Hubungan Pengetahuan Gizi dan Pekerjaan Ibu Terhadap Pemberian MP-ASI Dini di Puskesmas Telaga Biru Kota Pontianak Tahun 2014 - Eriza Wahyuhandani; Trias Mahmudiono (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2017)
Background : Giving the complementary foods is the determinant of optimal growth in children. A preliminary study in Telaga Biru Health centre showed that 10 out of 15 mothers has given her baby complementary food in early time, due to unknown factors, 3 out of 10 mothers who did were caused by working. It can be assumed that there is an influence of knowledge and mother’s work with early complimentary food giving. Objective : The goal of this research was to examine the relationship between the knowledge and the work of the mothers of 0-6 months aged babies towards giving early complementary foods in Telaga Biru Health centre, Pontianak.Methods: This is an observational analytic study with cross-sectional study design. The research population was all mothers whose babies ranged between 0-6 months in age within the work area of Telaga Biru Community Health Center of Pontianak City. Samples were obtained using simple random sampling technique with total 64 respondents. Statistic test used was linier regression with (α=0.05).Results: The result of the research showed that there was no relationship between the mother’s work through early complementary foods giving ( p=0.525), but in addition, there was a relationship between the knowledge through with early complementary feeding giving (p=0.003). This situation is evidence by the mother who has low knowledge, 69.2% giving thier baby complementary food in early time. The mother who has moderate knowledge, 33.3% giving their baby complementary food in early time, and the mother who has good knowledge was only 12.5% giving their baby complementary food in early time. Conclusion: The knowledge of mothers affects the early giving of complimentary food in breastfeeding. The higher the mother’s knowledge, the lesser likely the mother will give the early food complimentary in breastfeeding because mothers will apply their knowledge in giving the right food pattern for the babies. Therefore, it is needed to increase the level of knowledge of mothers to give the right complimentary food suited to the babies’ growth.ABSTRAKLatar Belakang: Pemberian makanan pendamping ASI merupakan salah satu faktor yang dapat mengoptimalkan tumbuh kembang anak. Hasil studi pendahuluan di puskesmas Telaga Biru Kota Pontianak menunjukan bahwa 10 dari 15 ibu telah memberikan MP-ASI secara dini kepada bayi karena faktor ketidaktahuan serta 3 diantara 10 ibu tersebut merupakan ibu bekerja. Dapat diasumsikan bahwa pengetahuan dan pekerjaan ibu mempengaruhi pemberian MP- ASI dini.Tujuan: Mengetahui hubungan pengetahuan dan pekerjaan ibu dengan pemberian makanan pendamping ASI secara dini di wilayah kerja Puskesmas Telaga Biru kota Pontianak.Metode: Jenis penelitian observasional analitik dengan rancangan penelitian cross sectional. Populasi penelitian yaitu seluruh ibu yang mempunyai bayi usia 0-6 bulan di wilayah kerja Puskesmas Telaga Biru Kota Pontianak. Sample diambil dengan teknik simple random sampling dengan besar sampel sebanyak 64 orang. Uji statistik yang digunakan adalah regresi linier (α=0,05).Hasil : Hasil penelitian menunjukkan bahwa tidak terdapat hubungan antara pekerjaan ibu dengan pemberian MP-ASI dini(P = 0,525 > 0,05), namun terdapat hubungan antara pengetahuan ibu dengan pemberian MP-ASI dini (P = 0,003 < 0,05). Hal ini dilihat dari ibu yang berpengetahuan kurang 69,2% memberikan MP-ASI dini. Ibu yang berpengetahuan cukup 33,30% memberikan MP-ASI dini, dan ibu yang berpengetahuan baik hanya 12,5% memberikan MP-ASI dini. .Kesimpulan: Pengetahuan ibu berpengaruh terhadap pemberian MP-ASI dini. Semakin baik pengetahuan maka ibu tidak akan memberikan MP-ASI dini karena ibu akan menerapkan pengetahuannya dalam membentuk pola makan yang benar pada bayi. Oleh karena itu diperlukan upaya peningkatan pengetahuan kepada ibu mengenai cara pemberian MP-ASI yang tepat.